On the Possible Cause of Sudden Storage Modulus Increase during the Heating of PM FeMnSiCrNi SMAs - Pricop, Bogdan; Grigoraș, Marian; Borza, Firuța; Özkal, Burak; Bujoreanu, Leandru-Gheorghe (MDPI AG, 2022)
A sudden increase in storage modulus (ΔE′) was repeatedly recorded during the heating of powder metallurgy (PM) 66Fe-14Mn-6Si-9Cr-5Ni (mass. %) shape memory alloy specimens subjected to dynamic mechanical analysis (DMA), under constant applied strain amplitude and frequency. This instability, exceeding 12 GPa, was associated with the reverse martensitic transformation of α′-body centered cubic (bcc) martensite to γ-face centered cubic (fcc) austenite, overlapped on a magnetic transition. This transition, observed by thermomagnetic measurements (T-MAG), was associated with the temporary spontaneous alignment of magnetic spins, which lasted until thermal movement became prevalent, during heating. ΔE′ was located around 250 °C on DMA thermograms and this temperature had the tendency to increase with the solution treatment temperature. On T-MAG diagrams, magnetization saturation temperature decreased from 405 °C to 52 °C with the increase in applied magnetic field from 20 Oe to 1 kOe and the increase in mechanically alloyed powder volume from 20% to 40%. On scanning electron micrographs, the presence of thermally induced α’-bcc martensite was emphasized together with the sub-bands that impede its stress-induced formation during DMA solicitation. On X-ray diffraction patterns of the solution-treated specimens, the presence of 22–82% α′-bcc martensite was identified, together with 8–55% retained austenite. It was assumed that the pre-existence of austenite together with α’-bcc martensite, in the microstructure of the solution-treated specimens, favored the magnetic transition, which destabilized the material and caused the storage modulus increase. The specimen comprising the largest amounts of austenite experienced the largest ΔE′.
Keywords: storage modulus; magnetization; Article; Chemistry; martensite plates; FeMnSi-based shape memory alloys; storage modulus; internal friction; magnetization; α’ martensite; martensite plates; lattice parameter; pre-strain; austenite; internal friction; QD1-999; α’ martensite; FeMnSi-based shape memory alloys